Spatiotemporal Dynamics of Global Agricultural Transport Greenhouse Gas Emissions from Trade and the Climate Implications of Localization Strategies - Zihan Gao (10820297) (2025)
Transportation has emerged as a major contributor to greenhouse gas (GHG) emissions worldwide. With increasing population growth and food demand, the spatial decoupling of production and consumption has intensified, driving a surge in transnational agricultural products transportation. However, existing research lacks a systematic assessment and future projection of GHG emissions from agricultural product transportation across multiple transport modes worldwide. To address this gap, we developed a global trade-linked transport GHG emission database by integrating multisource data and modeling frameworks. Compared with the research method in this paper, the previous great circle distance as the GHG emission of agricultural product transportation mileage was underestimated by 34%. This study systematically evaluates the spatiotemporal evolution of agricultural transport GHG emissions from 2000 to 2021 and explores their mitigation potential under future scenarios. Our findings reveal that global GHG emissions from agricultural transport increased by 1.6-fold over the 21-year period, with rising GHG emission intensity and trade density collectively shaping a high-carbon flow pattern dominated by exports from the Americas to Asia. Future scenario analyses indicate that the localization strategies proposed in this study are not particularly effective in reducing transport-related GHG emissions as inefficiencies inherent in localized agricultural production can increase production-stage emissions and, in turn, result in a net rise in total GHG outputs. These results suggest that future strategies should prioritize optimizing trade structures while simultaneously enhancing domestic agricultural productivity and promoting low-carbon farming technologies to achieve net emission reductions at the source.